PENGARUH MEDIA SOSIAL DALAM MENINGKATKAN KESADARAN MENGENAI KESEHATAN MENTAL REMAJA: SEBUAH TINJAUAN LITERATUR SISTEMATIS - Desi Permatasari (Jurnal Kesehatan, 2024)
Adolescent mental health is an important issue of global concern. Social media, which has become an integral part of adolescent life, has the potential to be a tool to raise awareness of mental health. This article aims to analyze the influence of social media in raising awareness of adolescent mental health through a systematic literature review (SLR). Literature searches were conducted on leading databases such as PubMed, Scopus, and Google Scholar using the keywords "social media", "mental health", "adolescents", and "awareness". Of the 200 articles found, 30 articles met the inclusion and exclusion criteria for further explanation. The results of the study indicate that social media has significant potential in raising adolescent awareness of mental health, although it also poses risks to their psychological well-being. This article concludes that proper use of social media can support efforts to promote adolescent mental health